The role of radiotherapy in soft tissue sarcomas. Retrospective study of 115 cases treated from 1979 to 1988. - Patrício, M. Brites; Trindade, M. Cândida; Santos, Filomena; Jorge, M. Leonor; Raposo, J. Silva; Neves, Miguel (Acta Médica Portuguesa, 1994)
In this study was analysed the results of a group of patients with soft tissue sarcomas treated at the IPOFG Center of Lisbon from January 1979 to December 1988. All these cases were referred to the Radiotherapy Department for radiation treatment, which was given in 84% of the patients as a complement to surgery and in 16% was either combined with chemotherapy or given as exclusive therapy. The immediate results showed complete remission in 79% and partial remission in 7% of the cases. Seventeen per cent of the patients developed relapses and 28% distant metastases after a free interval of 27.7 and 19.6 months respectively. The five year survival rates were 73.3% for the patients without recurrences, 55.4% for the patients with relapses and 21.4% for disseminated disease. The long term results varied according to the localization of the tumor, the stage of the disease, the age of the patient, the extension of surgery, the histologic type and the radiation dose. Five year survival rates also varied with the type of treatment (63.8% for surgery followed by radiotherapy with or without chemotherapy and 50.8% for preoperative radiotherapy and surgery with or without adjuvant chemotherapy). Radiotherapy with or without chemotherapy, in inoperable patients, was generally useful because it improved the quality of life, saving about 25% of the inoperable cases. Treatment related complications were minimal.